Nephrotic Syndrome in a 24-Year-Old Female with Myelodysplastic Syndrome: A Case Report - Cindy Yusliani; Ita Murbani Handajaningrum (HM Publisher, 2024)
Background: Nephrotic syndrome is rare in the normal population but is reported more frequently in patients with myelodysplastic syndrome (MDS). The pathogenesis is not clearly known, but it is thought to be related to immune dysregulation. Case presentation: We report a case of nephrotic syndrome in a 24-year-old woman with MDS. Patients complain of swelling, foamy urination, paleness, weakness, bleeding gums, and reddish spots on the body. Physical examination revealed hypertension, anemia, petechiae, and edema. Laboratory examination showed anemia, thrombocytopenia, hypoalbuminemia, dyslipidemia, and proteinuria. Abdominal ultrasound showed chronic processes in the kidneys, ascites, and pleural effusion. A renal biopsy showed membranoproliferative glomerulonephritis. Conclusion: Nephrotic syndrome in MDS patients is rarely reported, and its pathogenesis is still not clearly understood. Further research is needed to understand the pathogenesis and optimal therapeutic options.